The simplification of procedures in Portuguese administrative law - Jo\~ao Tiago Silveira; Tiago Fidalgo de Freitas; Gonçalo Fabi\~ao; Miguel Assis Raimundo (Administrative Sciences, 2022)
The present paper intends to provide an overview and a critical assessment of the administrative simplification policies implemented in Portugal over the past 20+ years. Throughout these decades, the major instruments for administrative simplification have been: (i) Decree-Law n. 135/99, of 22 April; (ii) the Simplex programme; (iii) the 2015 new Code of Administrative Procedure and its 2021 amendment; and (iv) the COVID-19 legislation. Although Decree-Law n. 135/99 (i) was the first attempt to specifically address simplification, it was a very thin one. The Simplex programme (ii), created in 2006, was the first cross-sectoral robust policy of simplification; its motto is "the simpler the better" and it encompassed reforms in all government areas aiming at cutting red tape, promoting administrative efficiency, and making the citizens' and the corporations' lives easier when dealing with State. The new Code of Administrative Procedure (iii), approved in 2015, brought about specific normative solutions to simplify procedures, namely, prior communications, administrative assistance, procedural conferences, and the electronic one-stop shop. Finally, the COVID-19 legislation (iv) was made necessary by the COVID-19 pandemic and by the fact that public health restrictions made it impossible for citizens to establish personal contact with the administration in many cases.
Keywords: 350; administrative efficiency; administrative procedure; administrative simplification; electronic procedure